A cardiac patch from aligned microvessel and cardiomyocyte patches. (23rd November 2017) - Schaefer, Jeremy A.; Guzman, Pilar A.; Riemenschneider, Sonja B.; Kamp, Timothy J.; Tranquillo, Robert T.
Abstract: Cardiac tissue engineering aims to produce replacement tissue patches in the lab to replace or treat infarcted myocardium. However, current patches lack preformed microvascularization and are therefore limited in thickness and force production. In this study, we sought to assess whether a bilayer patch composed of a layer made from human induced pluripotent stem cell‐derived cardiomyocytes and a microvessel layer composed of self‐assembled human blood outgrowth endothelial cells and pericytes was capable of engrafting on the epicardial surface of a nude rat infarct model and becoming perfused by the host 4 weeks after acute implantation. The bilayer configuration was found to increase the twitch force production, improve human induced pluripotent stem cell‐derived cardiomyocyte survival and maturation, and increase patent microvessel lumens compared with time‐matched single layer controls after 2 weeks of in vitro culture. Upon implantation, the patch microvessels sprouted into the cardiomyocyte layer of the patch and inosculated with the host vasculature as evidenced by species‐specific perfusion labels and erythrocyte staining. Our results demonstrate that the added microvessel layer of a bilayer patch substantially improves in vitro functionality and that the bilayer patch is capable of engraftment with rapid microvessel inosculation on injured myocardium. The bilayer format will allow for scaling up in size through the addition of layers to obtain thicker tissues generating greater force in the future.